The Relationship Between Work Family Conflict and Internal Locus of Control With Retail Employee Burnout - Sucipto, Gita Novelia; Noviekayati, IGAA; Ema Mustikawati Ningdyah, Anrilia (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to prove the relationship between work family conflict and internal locus of control with burnout of retail employees. The subjects of this study were 180 retail employees who were experiencing burnout. The approach used in the study was a quantitative approach with a data collection method using a scale that had been tested for validity and reliability. Data analysis was carried out using a multiple linear regression analysis correlation test. The measuring instruments used were the burnout scale, the work family conflict scale and the internal locus of control scale. The results showed that there was a correlation between work family conflict and internal locus of control with burnout of retail employees. Work family conflict showed a positive and significant correlation with burnout of retail employees, while internal locus of control showed a negative and significant correlation with burnout of retail employees. The results showed that work family conflict can increase the level of burnout of retail employees while internal locus of control can minimize the level of burnout of retail employees.